Glossina fusca group tsetse as vectors of cattle trypanosomiasis in Gabon and Zaire - Leak, S.G.A.; Colardelle, C.; D'Ieteren, G.D.M.; Dumont, P.; Feron, A.; Jeannin, P.; Minengu, M.; Mulungo, M.; Ngamuna, S.; Ordner, G.; Sauveroche, B.; Trail, J.C.M.; et al. (Wiley, 1991)
The significance of Glossina fusca group tsetse flies as vectors of cattle trypanosomiasis was examined using biconical traps to survey tsetse populations at one site in Gabon and two sites in Zaire. Mean trypanosome infection rates in G. tabaniformis Westwood over the study period ranged from 8.9 - 17.7 percent at the two sites. The mean infection rate in G. nashi Potts was 6 percent. Up to 49 percent of bloodmeals of G. tabaniformis were from cattle. Trypanosome prevalence in cattle where G. tabaniformis appeared to be the main vector was 9.5 percent and 5.4 percent at the Mushie and OGAPROV ranches respectively. A highly significant positive correlation was found between tsetse challenge and trypanosome prevalence in N'Dama cattle across sites. Tsetse challenge was defined as the product of tsetse relative densities, trypanosome infection rates in the flies and the proportion of feeds taken by them from cattle. Thus G. tabaniformis can be an important vector of pathogenic Trypanosoma species in cattle.